STUDI PERKEMBANGAN SUBSTANSI KUTIPAN AKTA PERKAWINAN BAGI NON MUSLIM SETELAH BERLAKUNYA UNDANG UNDANG NOMOR 1 TAHUN 1974 PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN BANYUMAS - Trusto Subekti (Faculty of Law, Universitas Jenderal Soedirman, 2010)
Article 2 paragraph (2) Law No.1 of 1974 stated that every marriage must be recorded as evidence of the Marriage Certificate issued. Viewed from the aspect of history, marriage records still reflect the political classification of residents based on the Civil Ordinance for the European group No. S.1849. 25, Civil Ordinance for the Chinese S. No. 1917. 1919 No. 130 Jo. 81, Civil Ordinance for class citizen Christian Original S. No. 19,330. 1936 No. 75 Jo. 607. In Indonesia the law of political developments have led to no longer recognize classification population. Since 1966, has issued instructions of the Cabinet Presidium Ampera No. 31/U/IN/12/1966 and followed-up by the Presidential Decree No.12 Year 1983, and finally Law No. 23 Year 2006 concerning Population and Administrative and Regulation No.37 Year 2007 as its implementing regulations. Recording of marriage is a state of institutional behavior and decision or reflect the will of the state establishment, and the product of a decision or other form of establishment of the Marriage Act and Marriage Act quotation. If the Marriage Act's passage can be read law and political unknown and the state of institutional readiness in implementing its mission. This study aims to determine the development of the Marriage Act Excerpt substances, particularly applicable to non-Muslim population The approach used in research is a normative juridical and the results obtained is that the study of the development of the Marriage Act Excerpt substance for non-Muslims in touch with the historical aspects that show the existence of variation.Keywords: Growth, Quotes Marriage Act, Non-Muslims